LITERATURE REVIEW OF EMOTIONAL INTELLIGENCE AND PSYCHOLOGICAL WELL-BEING - Siti Hajar Muhammad Syafiq Tan; Noor Hafikah Othman; Nur Izzati Syahirah Mohd Salleh; Puteri Adriana Zakirah Mohd Azri; Nur Aqilah Adeline Badarul Hissam; Syahrina Hayati Md Jani (International Journal of Accounting, Finance and Business, 2022)
This paper reviews the idea of emotional intelligence and terms such as intelligence, emotion, and emotional intelligence. A distinction will be made between the various theories of emotional intelligence, the one that emphasises mental ability from those that mix mental capabilities with personal traits. This paper claims that Mayer and Salovey’s definition of emotional intelligence is appropriate to be a model that can explain emotional intelligence among adolescents. Emotional intelligence as the capability to understand and control one’s emotions is an ability that can be learned and enhanced where the level of an individual’s emotional competence increases with age. Next, the purpose of this review is to reveal the existing literature on the definition as well as the relationship of emotional intelligence and psychological well-being. Specifically, this paper reviews the literature on the relationship between emotional intelligence and psychological well-being; relationship between emotional intelligence and perceived social support; and relationship between emotional intelligence and perceived stress. The review will give a holistic understanding of the emotional intelligence, psychological well-being, perceived social support, and perceived stress concepts for future researchers and aid to identify the research gap.